PELAKSANAAN PEMBERDAYAAN ANAK TERLANTAR DAN REMAJA PUTUS SEKOLAH DI PANTI SOSIAL BINA REMAJA RUMBAI KOTA PEKANBARU TAHUN 2011-2015 - Dede Yaksan; Baskoro Wicaksono (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
The background of this study was to describe the implementation of empowerment regarding the abandoned children and adolescents drop out of school at the Young Children's Social Development in 2011-2015. How the implementation of the empowerment of displaced children and adolescents out of school in the Panti Sosial Bina Remaja Rumbai Pekanbaru and supporting factors and obstacles anything in the implementation of the empowerment of displaced children in Children's Social Development Youth Rumbai Pekanbaru and seeks to know the empowerment process conducted by the Social Institution Bina Youth Tassel City Pekanbaru kepapa neglected children and adolescents drop out of school. As well as knowing what are the supporting factors and obstacles in the gudgeon waif and dropout.This type of research is descriptive qualitative study aimed to describe the real state of the field systematically and accurately related facts and research analysis unit, as well as field observations based on data (information) in particular. Methods of data collection is by interview, documentation and observation.The results showed that: Implementation of coaching waif includes delivery of content using simple language and interspersed with examples of everyday life, the method used is the method of lecture, discussion, question and answer, and practice as well as instructional media used such as modules, leaflets and films , The attitude of supervising the development activities are also friendly, humorous, firm and familiar. environment / atmosphere for learning yangmenyenangkan make children do not feel bored in following the activities. Factors supporting the coaching is the cooperation between partners and external parties / institutions in the implementation of the development, availability of infrastructure implementation guidance. In the process of empowerment there are still some problems that become obstacles in the empowerment of displaced children and adolescents drop out of school. As the need for updates and additional facilities and infrastructure skills to children so that is expected to deliver maximum results to the child.Keywords: Implementation Empowerment, Neglected Children, Youth Dropout.